2010
DOI: 10.1002/eat.20737
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with body dissatisfaction and disordered eating in women in midlife

Abstract: This study provides support for the role of developmentally relevant factors in body dissatisfaction and disordered eating in midlife women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 49 publications
4
68
2
4
Order By: Relevance
“…42 The present survey showed that age did not demonstrate any impact an the scores on the questionnaire EDI, except that the younger group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) showed significantly higher scores than the middle aged group (40-49) on subscale bulimia on the questionnaire EDI-2. Mclean, Paxton and Wertheim found that in the EDE-Q subscales: the Body Dissatisfaction and disordered eating symptoms were unrelated to age 13 . Johnson and Bedford's study in Canada across gender and age groups, demonstrated that age was partly significantly correlated with the scores on the questionnaire EAT 12 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…42 The present survey showed that age did not demonstrate any impact an the scores on the questionnaire EDI, except that the younger group (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) showed significantly higher scores than the middle aged group (40-49) on subscale bulimia on the questionnaire EDI-2. Mclean, Paxton and Wertheim found that in the EDE-Q subscales: the Body Dissatisfaction and disordered eating symptoms were unrelated to age 13 . Johnson and Bedford's study in Canada across gender and age groups, demonstrated that age was partly significantly correlated with the scores on the questionnaire EAT 12 .…”
Section: Discussionmentioning
confidence: 97%
“…Johnson and Bedford explored that young participants (18-34 years) (both genders) showing significantly high levels of food preoccupation and image preoccupation on the questionnaire EAT, in comparison with those in the 35-64 years group and over 65 years group 12 . Although women in midlife showed frequent Body Dissatisfaction and disordered eating, research on variables related to these attitudes and behaviors was limited 13 . Developmental factors are also likely to be associated with Body Dissatisfaction and disordered eating in midlife 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors could reduce the attention given to "appearance", body image and aging by the women presenting the above mentioned characteristics [82]. On the contrary, the signs of aging (wrinkles, hair loss, changes to body fat distribution) [83] and the emphasis given to appearance, self-care and body mass index, represent risk factors for body dissatisfaction [84]. The fear of aging has been positively related to disordered/disinhibited eating and drive for thinness in middle-aged women.…”
Section: Midlife and Late-life Eating Disordersmentioning
confidence: 99%
“…Nearly three quarters of a sample of women over the age of 50 were trying to lose weight and reported using the following extreme behaviours in the previous 5 years: diet pills, excessive exercise, diuretics, laxatives, and vomiting (Gagne et al, 2012). Indeed, research indicates that body dissatisfaction experienced by women in midlife has also been associated with disordered eating (McLean et al, 2010). Nearly a third of a sample comprised of 500 middle-aged women felt dissatisfied with their eating patterns, whilst more than 10% of the women supported the use of restricted eating to control their weight (Marcus et al, 2007).…”
mentioning
confidence: 99%